2006
DOI: 10.1002/pssb.200541167
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magnetotransport properties in (LaxSm1–x)2/3Sr1/3MnO3 (x = 1/3, 1/2 and 2/3) manganites

Abstract: The magnetic and transport properties of (La x Sm 1-x ) 2/3 Sr 1/3 MnO 3 (x = 1/3, 1/2 and 2/3) manganites, prepared by the citrate-gel route, have been investigated. These compounds are found to crystallize in the orthorhombic structure. The hopping between Mn 3+ and Mn 4+ sites is controlled by the Mn -O -Mn bond angle. The magnetoresistance in 8.5 kOe fields varies from 15 to 25 percent over the temperature range 300 K to 80 K. The conduction mechanism can be understood by using the correlated small polaron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The sintered samples contain only one phase, with orthorhombic structure (Pnma space group) (see Fig. 1), in agreement with the available data [7]. The micrographs of the manganites indicated also the presence of only one phase and a significant increase of the average size of the crystallites with the increase of the Cu content in the samples (results will be published).…”
Section: Resultssupporting
confidence: 87%
“…The sintered samples contain only one phase, with orthorhombic structure (Pnma space group) (see Fig. 1), in agreement with the available data [7]. The micrographs of the manganites indicated also the presence of only one phase and a significant increase of the average size of the crystallites with the increase of the Cu content in the samples (results will be published).…”
Section: Resultssupporting
confidence: 87%
“…xFexO3) [37] and Mn substitution at the Fe site (SrFe12-xMnxO19) has brought a reduction in the Ms values [31]. Ideally, the saturation magnetization of the composite consisting of hard and soft phases can be measured as [15,38] M = Ms,hard (1−fs) + Ms, soft × fs (1) where Ms,hard is the saturation magnetization of hard-phase SFO, Ms,soft is the saturation magnetization of soft-phase LSMO, and fs is the weight fraction of the soft phase in the composite. The measured value of 34.93 emu/g for the Ms of the composite with 40 wt % LSMO is about 38% lower than that predicted by Equation (1).…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, the saturation magnetization of the composite consisting of hard and soft phases can be measured as [15,38] M = Ms,hard (1−fs) + Ms, soft × fs (1) where Ms,hard is the saturation magnetization of hard-phase SFO, Ms,soft is the saturation magnetization of soft-phase LSMO, and fs is the weight fraction of the soft phase in the composite. The measured value of 34.93 emu/g for the Ms of the composite with 40 wt % LSMO is about 38% lower than that predicted by Equation (1). Most likely, the intermixing of atoms, as discussed above, could be the factor for the observed deviation in the Ms value as compared to that of projected by Equation (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DE interaction, which favors ferromagnetic (FM) and metallic behavior, competes with the Jahn-Teller (JT) effect which favors antiferromagnetic (AFM) and insulating behavior. Recent studies have shown that DE alone cannot explain various physical properties of manganites [2] and other effects such as charge ordering, average Asite cationic radius <r A > , A-size cationic size mismatch [3,4], etc. also play important roles.…”
Section: Introductionmentioning
confidence: 99%